Al-Farabi's ideals and intercultural competence (Journal of Philosophy Culture and Political Science, 2015)
Al-Farabi's doctrine about virtuous city, virtuous people, virtuous land has much in common with the modern ideals of a culture of peace.Public life can be turned on a reasonable basis. The fundamental values of culture world- human community built on friendship and love, tolerance (tolerance, acceptance and respect for Others), respect for the rights of another (human rights), the establishment of the rule of law and civil society. Discourses of the East, West, North and South - is not only independent autonomous archetypes and associated structures in a philosophical dialogue and intercultural communication.
Keywords: a virtuous city; culture of peace; East; West; North; South; intercultural competence; transmodern; systemic phenomenology.